THE MODIFICATION OF THE POLYMER COMPOSITION TO EXPAND THE FUNCTIONAL PROPERTIES OF REPAIR COMPOUNDS - Prykhodko, O. P.; Kharchenko, Ye. S.; Krasniuk, A. V. (Science and Transport Progress, 2009)
The modification of polymer composition containing epoxide resin, amine hardener, alcohol-and-acetone solvent, and filler – dust of gas cleaning of ferrosilicium treatment – was performed. On the basis of analysis of experimental results the optimum compositions were chosen on the strength indices of polymer stone, in doing so the technological features of polymer mixture and cost of compositions were taken into account.